2021
DOI: 10.3390/ijms222312799
|View full text |Cite
|
Sign up to set email alerts
|

Biosorption of Zn(II) from Seawater Solution by the Microalgal Biomass of Tetraselmis marina AC16-MESO

Abstract: Biosorption refers to a physicochemical process where substances are removed from the solution by a biological material (live or dead) via adsorption processes governed by mechanisms such as surface complexation, ion exchange, and precipitation. This study aimed to evaluate the adsorption of Zn2+ in seawater using the microalgal biomass of Tetraselmis marina AC16-MESO “in vivo” and “not alive” at different concentrations of Zn2+ (0, 5, 10, and 20 mg L−1) at 72 h. Analysis was carried out by using the Langmuir … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Owing to their significance in the element elimination experiment, trace metals were used in the final medium at the original concentration instead of being removed. Essentially, trace metals are essential components for cell growth [ 16 ]. The Tris base, NH 4 Cl, MgSO 4 , and AcOH had negative effects, whereas CaCl 2 and potassium phosphate had positive effects ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Owing to their significance in the element elimination experiment, trace metals were used in the final medium at the original concentration instead of being removed. Essentially, trace metals are essential components for cell growth [ 16 ]. The Tris base, NH 4 Cl, MgSO 4 , and AcOH had negative effects, whereas CaCl 2 and potassium phosphate had positive effects ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding other potential biotechnological applications, it is important to highlight the results obtained by the research group concerning its tolerance and potential use in heavy metal contamination remediation. The strain has shown high removal efficiency of Cu 2+ , Fe 3+ , and Mn 2+ as well as its potential as a bioabsorbent to remove Zn 2+ from industrial effluents [17,85].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Huarachi‐olivera et al. (2021) studied the biosorption efficacy of zinc using Tetraselmis marina AC16‐MESO from the seawater solution. Their investigation showed that at the initial concentration of 0–20 mg/L Tetraselmis marina AC16‐MESO bio‐absorbed zinc from seawater solutions.…”
Section: Microalgae‐based Wastewater Bioremediation Approachmentioning
confidence: 99%